A comparison of the knowledge of hormonal contraception between women living in urban and rural areas of Poland - Joanna Witkoś; Magdalena Hartman-Petrycka; Grzegorz Błażejewski (PLoS ONE, 2025)
The Contraception Policy Atlas and its latest 2024 study shows that the availability of contraception in Poland is a meagre 33.5%, the lowest of all European countries. The aim of the research, therefore, was to assess and compare the knowledge of women, living in rural and urban areas of Poland, about the modern methods of the hormonal contraception (HC) they use, includes all hormonal methods (pill, implant, patch, etc.). The study involved 239 women. The research was conducted using an online survey distributed to the public via community forums. The most commonly used method of HC was the combined pill, with 62.27% of the women surveyed using this type of contraception. None of the women surveyed used the emergency contraceptive pill. This finding is concerning given the broader context of contraceptive use in Poland. There were differences in the reasons for contraceptive use according to the place of residence. Women living in rural areas were less likely to use HC to relieve menstrual pain (28.81%) than those living in small and medium-sized towns (47.87%), and also less likely to use HC to regulate their menstrual cycle (27.12%) than those living in small and medium-sized towns (42.55%). Despite the fact that all the women who participated in this study were using HC, 13.39% stated that they did not know how this type of medication affects the female body. There was a tendency for women living in rural areas (20.34%) to be more likely to say ‘don’t know’ than the women from large towns (9.20%). The most commonly indicated side effect of contraceptives on the female body was an increased risk of thromboembolic events (70.71%).